2020
DOI: 10.7717/peerj.9257
|View full text |Cite
|
Sign up to set email alerts
|

Bee diversity in secondary forests and coffee plantations in a transition between foothills and highlands in the Guatemalan Pacific Coast

Abstract: Background Although conservation of pristine habitats is recognized in many countries as crucial for maintaining pollinator diversity, the contribution of secondary forest conservation is poorly recognized in the Latin American context, such as in Guatemala. San Lucas Tolimán (SLT) is a high-quality coffee production region from the Atitlan Province, which has the second highest deciduous forest cover in Guatemala and pristine forest is prioritized for conservation. In contrast, secondary forest protection is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The provision of high flower diversity to pollinator communities may mitigate the negative impacts of landscape perturbation on pollinator diversity (Bates et al, 2011;Birdshire et al, 2020). In addition, it has been demonstrated that agroforestry systems in the tropics where non-intensive agriculture is performed, play an important role in the conservation of pollinator diversity (Jha and Vandermeer, 2010;Landaverde-González et al, 2017;Vides-Borrell et al, 2019;Armas-Quiñonez et al, 2020) and plant-pollinator interactions (Klein et al, 2008;Perfecto et al, 2014;Escobedo-Kenefic et al, 2020) Also, tropical croplands are immersed in topographically diverse areas that may promote complex interactions among the habitat, pollinator diversity and plant-pollinator interaction systems, at landscape and local scales (Klein et al, 2008;Motzke et al, 2016;Cely-Santos and Philpott, 2019;Wayo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The provision of high flower diversity to pollinator communities may mitigate the negative impacts of landscape perturbation on pollinator diversity (Bates et al, 2011;Birdshire et al, 2020). In addition, it has been demonstrated that agroforestry systems in the tropics where non-intensive agriculture is performed, play an important role in the conservation of pollinator diversity (Jha and Vandermeer, 2010;Landaverde-González et al, 2017;Vides-Borrell et al, 2019;Armas-Quiñonez et al, 2020) and plant-pollinator interactions (Klein et al, 2008;Perfecto et al, 2014;Escobedo-Kenefic et al, 2020) Also, tropical croplands are immersed in topographically diverse areas that may promote complex interactions among the habitat, pollinator diversity and plant-pollinator interaction systems, at landscape and local scales (Klein et al, 2008;Motzke et al, 2016;Cely-Santos and Philpott, 2019;Wayo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This may be related not only to the high plant species richness, typical of intermediate successional stages, but also to the diversity of plant growth forms found there (Roberts et al 2017;Fahrig et al 2019). This pattern was also detected in studies where intermediate disturbances and edge effects, in some cases, benefited the supply of floral resources and increased the diversity of bee species (Hadley and Betts, 2012;Fisher et al 2017;Landaverde-González et al 2017;Armas-Quiñonez et al 2020). These results highlighted the importance of forest conservation for the provision of nesting resources for these stingless bee species and encourage the advancement of the succession of secondary forests, which are fundamental in the provision of floral resources for bees.…”
Section: Relationship Between Vegetation Coverage and Floral Preferencesmentioning
confidence: 64%
“…Moreover, the effects of changes in seasons linked to the availability of resources have been evidenced in several investigations (Do Nascimento and Nascimento 2012;Samnegård et al 2015;Armas-Quiñonez et al 2020;Theodorou et al 2020), where bottom-up effects (from flowering plants to bees) were highlighted. The behaviour, diversity, and foraging activity of bees are addressed by the flowering seasons, availability, and quality of floral resources.…”
Section: Relationship Between Vegetation Coverage and Floral Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we observed that the relationship between behaviour variables and fruit production presented the same trend for both agroecological and conventional management, which is in line with the lack of effect of management on community composition, richness and behavioural variable of floral visitors observed in this study. Diverse studies had already showed that species richness was positively related to fruit production, where stingless bees were normally the second most abundant species after A. mellifera (Armas‐Quiñonez et al 2020; Garibaldi et al 2013; Klein et al 2003b; Munyuli 2014; Vergara & Badano 2009; Winfree et al 2007), suggesting that wild bees are also responsible for pollination. Similarly, other studies comparing apis and non‐apis behaviour showed that non‐apis bees presented behaviour that was more efficient, even in the presence of large amounts of honeybees (Miñarro & Twizell 2015) and that an increase of 80% in crop yield was related to the density of non‐managed, social floral‐visiting bees per coffee shrub (Veddeler et al 2008) and to their degree of sociability (Munyuli 2014).…”
Section: Discussionmentioning
confidence: 99%